Calcium Channels in Postnatal Development of Rat Pancreatic Beta Cells and Their Role in Insulin Secretion - García-Delgado, Neivys; Velasco, Myrian; Sánchez-Soto, Carmen; Díaz-García, Carlos Manlio; Hiriart, Marcia (Frontiers in Endocrinology, 2018)
Pancreatic beta cells during the first month of development acquire functional maturity, allowing them to respond to variations in extracellular glucose concentration by secreting insulin. Changes in ionic channel activity are important for this maturation. Within the voltage-gated calcium channels (VGCC), the most studied channels are high-voltage-activated (HVA), principally L-type; while low-voltage-activated (LVA) channels have been poorly studied in native beta cells. We analyzed the changes in the expression and activity of VGCC during the postnatal development in rat beta cells. We observed that the percentage of detection of T-type current increased with the stage of development. T-type calcium current density in adult cells was higher than in neonatal and P20 beta cells. Mean HVA current density also increased with age. Calcium current behavior in P20 beta cells was heterogeneous; almost half of the cells had HVA current densities higher than the adult cells, and this was independent of the presence of T-type current. We detected the presence of α1G, α1H and α1I subunits of LVA channels at all ages. The Cav 3.1 subunit (α1G) was the most expressed. T-type channel blockers mibefradil and TTA-A2 significantly inhibited insulin secretion at 5.6 mM glucose, which suggests a physiological role for T-type channels at basal glucose conditions. Both nifedipine and TTA-A2, drastically decreased the beta cell subpopulation that secretes more insulin, in both basal and stimulating glucose conditions. We conclude that changes in expression and activity of VGCC during the development play an important role in the physiological maturation of beta cells.